PENGARUH KARAKTERISTIK PETANI TERHADAP IMPLEMENTASI KARTU TANI - Dini Lestari; D Yadi Heryadi; Ulpah Jakiyah (Melati Institute, 2023)
The farmer card is one of the government programs in fulfilling the distribution of subsidized fertilizers to be right on target. Almost all farmers in Sodonghilir Village have received farmer cards, but not all farmers have utilized the farmer cards with various arguments of obstacles faced including the socio-economic conditions of farmers. This study aims to determine the effect of farmer characteristics on the implementation of farmer cards in Sodonghilir Village, Sodonghilir District, Tasikmalaya Regency. The research method used is a survey method. The analytical tool used is quantitative descriptive analysis using multiple linear regression analysis. The results showed that farmer characteristics simultaneously had a positive influence on the implementation of farmer cards in Sodonghilir Village, Sodonghilir District, Tasikmalaya Regency by 54.4%. Partially, the variable of land area has a positive and significant influence on the implementation of farmer cards while the variables of age, education, farming experience and farmer income have no influence on the implementation of farmer cards in Sodonghilir Village, Sodonghilir District, Tasikmalaya Regency.